GeoGebra y el aprendizaje significativo en matemáticas de los estudiantes de décimo año de educación general básica - García Abarca, Julia María (2023)
The present research focused on identifying the relationship of GeoGebra software with the significant learning in Mathematics of tenth year students of basic general education. The study has an exploratory approach of descriptive type, based on a documentary and field research, in which a bibliographic review of primary and secondary sources was carried out, to identify theoretical conceptualizations of empirical works related to GeoGebra software in educational contexts. On the other hand, the collection of information consisted of using a search log, content sheets, an observation sheet and a learning test applied to students. The documentary results show that GeoGebra is an interactive and dynamic software that favors significant learning, since this tool facilitates the visualization, interaction and analysis of different mathematical constructions, also, it improves the student's skills through practice, thus, with the results of the field study it was concluded, that there is no clear relationship between the GeoGebra tool and the significant learning of the students of the tenth year of basic education. Key words: Educational Technology, Teaching, Meaningful Learning, GeoGebra, Mathematics.